Efficiency Of Some Combinations Of Planting Media Against Growth And Yield Of Red Lettuce Plants (Lactuca sativa VAR. Red Rapids) - Riven Sadil; Bobby J. V. Polii; Tommy B. Ogie (Jurnal Agroekoteknologi Terapan, 2022)
The purpose of this study is to obtain an efficient combination of planting media for the growth and yield of vegetables, especially the Red Lettuce plant (Lactuca sativa var Red rapids). This research was carried out at the Greenhouse of the Faculty of Agriculture, Sam Ratulangi University from July to September 2022. This study used a non-factorial Complete Randomized Design (RAL) which was carried out with 5 treatments and 4 tests. So there are 20 experimental units. M0 (Soil without combination) as a control, M1(Combination of Soil and Husk), M2 (Combination of Soil and Husk Charcoal), M3(Combination of Soil and Sawdust) and M4 (Combination of Soil and Burn Sawdust). The results showed that the M4 treatment (Combination of Soil and Burn Sawdust) gave the best plant height with an average of 18.13 cm, the average number of leaves was 19.00 strands, the average brangkasan weight was 97.75 grams, the wet weight of the roots averaged 3.75 grams and based on the Fingerprint Analysis had a noticeable influence on the number of leaves, leaf width and weight of the Red Lettuce plant (Lactuca sativa var. Red rapids). Keywords: Growing media, combination, Lactuca sativa var. Red rapids Abstrak Tujuan dari penelitian ini adalah untuk mendapatkan kombinasi media tanam yang efisien untuk pertumbuhan dan hasil sayuran khususnya tanaman Selada Merah (Lactuca sativa var Red rapids). Penelitian ini dilaksanakan di Rumah Kaca Fakultas Pertanian Universitas Sam Ratulangi pada bulan Juli sampai September 2022. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) non faktorial yang dilakukan dengan 5 perlakuan dan 4 pengujian. Jadi terdapat 20 satuan percobaan. M0 (Tanah tanpa kombinasi) sebagai kontrol, M1 (Kombinasi Tanah dan Sekam), M2 (Kombinasi Tanah dan Arang Sekam), M3 (Kombinasi Tanah dan Serbuk Gergaji) dan M4 (Kombinasi Tanah dan Serbuk Gergaji Bakar). Hasil penelitian menunjukkan bahwa perlakuan M4 (Kombinasi Tanah dan Serbuk Gergaji Bakar) memberikan tinggi tanaman terbaik dengan rata-rata 18,13 cm, rata-rata jumlah daun 19,00 helai, berat brangkasan rata-rata 97,75 gram, berat basah akar rata-rata 3,75 gram dan berdasarkan Analisa Sidik Jari berpengaruh nyata terhadap jumlah daun, lebar daun dan berat tanaman Selada Merah (Lactuca sativa var. Red rapids). Kata kunci: Media tanam, kombinasi, Lactuca sativa var. Red rapids